Risk factors for incomplete excision of cutaneous squamous cell carcinoma: A single-center study performed on 1082 excisions in Northern Italy - S.C. van Helmond; S. Cozzi; B. Breugelmans; D. Codazzi; L. Valdatta; M. Carminati (JPRAS Open)
Summary: Cutaneous squamous cell carcinoma, which makes up for 25% of keratinocyte carcinomas, is the second most frequent skin cancer worldwide. Surgical excision via a clinical and microscopic complete resection is the treatment of choice. Incomplete excisions carry the risk of local recurrence, deep subclinical progression, and metastasis. This retrospective cohort study aimed to investigate the risk factors associated with the incomplete excision of cutaneous squamous cell carcinoma. This series included 837 patients who underwent surgical treatment for 1082 primary cutaneous squamous cell carcinoma in the Plastic Surgery Department of the Papa Giovanni XXIII Hospital in Bergamo, Northern Italy between 2012 and 2021. Patient-, procedure-, and tumor characteristics were collected and analyzed. Incomplete excision rate was 11.8% (n=128). The Pearson chi-squared test and univariable logistic regression showed tumor diameter [cm] (p<0.001), tumor thickness [mm] (p<0.001), tumor location (ear p=0.006, peri-orbital, p=0.029), differentiation grade (G3=0.005), infiltration level (hypodermis, p<0.001; muscle, p=0.013; bone/ cartilage p<0.001), presence of perineural invasion (p=0.041), ulceration (p=0.010), no prior diagnostic biopsy (p=0.041), and additional samples taken (p<0.001) with additional samples not free of tumor cells (p<0.001) to be significant risk factors/ predictors for incomplete excision. Risk factors should be considered in the management of cutaneous squamous cell carcinoma. This study documented several key contributions and confirmations regarding the risk factors associated with incomplete excision in cutaneous squamous cell carcinoma by comprehensively analyzing of one of the largest cohort studies in the field.